A new xerophytic species of Mimosa (Mimosoideae, Leguminosae) from Madagascar - Morales, Matías; Fortunato, Renée H. (Phytotaxa, 2016)
A new Malagasy species, Mimosa dupuyana, is described and illustrated. This species is closely related to M. delicatula, but they can be distinguished by the leaf formula, leaf morphology and pods. M. dupuyana has leaves with broad, flattened, and dorsiventrally compressed petioles and only 2–3 leaflet pairs, while M. delicatula has narrow, terete to subteretepetioles and 5–9 leaflet pairs. In addition, the pods of Mimosa dupuyana are constricted between seeds, coriaceous, reddish and elevated on each seeds. The latter species is quite different to the remainder known Malagasy species of Mimosa, by combination of some or all of these characters: leaf-formula, habit, form of petioles, and form and armament of pods. Together, M. delicatula and M. dupuyana resemble some lineages of South American section Batoucalon series Farinosae, which occur in seasonally dry subtropical formations, and this could be an interesting example of convergent evolution. Illustrations, keys for identification and taxonomical, distribution and ecological comments are included.